Emotional Intelligence and Academic Achievement of Psychology Students : Kecerdasan Emosional dan Prestasi Akademik Mahasiswa Psikologi - Indriani, Erry (Psikologia : Jurnal Psikologi, 2025)
Student academic achievement is often understood solely as a result of intellectual intelligence. However, success in higher education is also influenced by non-cognitive factors, one of which is emotional intelligence. This study aims to explore the relationship between emotional intelligence and academic achievement of Psychology students at University X through a qualitative approach. The case study approach is used to gain a deep understanding of students' subjective experiences in managing emotions, maintaining motivation, and building social relationships within an academic context. Research participants were selected using purposive sampling, consisting of active students who had completed at least four semesters with varying Cumulative Grade Point Averages (CGPA). Data were obtained through in-depth interviews, focus group discussions (FGDs), and academic documentation, and then analyzed using thematic analysis techniques. The research findings revealed four main themes closely related to students' academic achievement, namely: emotional regulation skills in dealing with academic pressure, intrinsic motivation and perseverance in learning, empathy and social support that strengthen academic networks, and social skills that open up broader academic opportunities. Students with high emotional intelligence have been proven to be more capable of managing stress, maintaining learning motivation, building positive relationships, and performing confidently in academic settings. The integration of these four aspects shows that emotional intelligence is not merely a supplement but an essential foundation in supporting academic achievement. This finding suggests that universities should develop programs to enhance emotional intelligence, including emotion regulation training, peer mentoring, and social skills workshops. Thus, improving emotional intelligence can be an effective strategy to enhance both academic achievement and the professional readiness of Psychology students at University X. Highlights: Emotional intelligence strongly supports stress management, motivation, and social relations. Four key themes: regulation, motivation, empathy, and social skills. Universities should design programs to enhance emotional intelligence. Keywords: Academic Achievement, Emotion Regulation, Emotional Intelligence, Intrinsic Motivation, Psychology Students.